PENGARUH BERAT MEDIA DAN INTERVAL PEMBERIAN PUPUK CAIR TERHADAP PERTUMBUHAN DAN HASILTANAMAN PAKCHOY DALAM POLIBAG - Haryuni Haryuni; Teguh Supriyadi; Tyas Soemarah Koernia Dewi (JURNAL ILMIAH AGRINECA, 2017)
Fusarium oxysporum f.sp. vanillae is a pathogenic fungi for vanili plants. The fungi have chitin cell wall that can be degraded by chitinase from chitinolytic  Rhizoctonia binucleate of fungi. Aim of this research was determine how the interaction between the  F. oxysporum f.sp. vanillae  and Rhizoctonia binucleate were isolated from plant rizosfere. Chitinolytic activity were measured based on the clear zone around the colony in chitin medium. Interaction of fungi were determined by an antagonistic test. This research showed that Rhizoctonia binucleate  is  chitinolytic,  antagonist and alternative of biofungiside to F.oxysporum f.sp. vanillae.